A TISM approach for the analysis of enablers in implementing mass customization in Indian manufacturing units. Issue 2 (25th January 2023) - Jain, Piu; Garg, Suresh; Kansal, Gayatry
Abstract: Mass Customization is a generic business strategy for organizational excellence and organizations striving for competitive advantage are incorporating MC into their business model. Though research has been done to identify enablers of mass customization, there has been an associated degree of study in conceptual papers while theory-building articles are less in number. Also, less study has been done in the Indian market scenario. The literature show that organizations are apprehensive of their technological potentials and are not taking initiative to transform themselves from conventional mass manufacturing companies to mass customization for emerging market needs. As a response to this research gap, a systematic literature review is conducted on enablers for MC and Total Interpretive Structural Modelling (TISM) and MICMAC analysis is used to develop a framework that illustrates how enablers are placed at different levels and how a particular enabler influences the other or getting influenced. Supporting this insight, a theory for accomplishing mass customization in manufacturing units is established. The theory is verified from experts by structured questionnaire from three Indian manufacturing companies where Mass customization is being practiced. This paper renders a summary of the methodology and specifies its validation in three case study companies. Practices are suggested to reinforce the attainment of mass customization in organizations aspiring to implement mass customization.